The Effect on Net Photosynthesis of Pedigree Selection for Low and High Rates of Photorespiration in Tobacco - Zelitch, Israel (1973)
A normal appearing plant with a low rate of photorespiration (ratio of (14)CO(2) released light/dark = 1.6) was found in an unselected tobacco (Nicotiana tabacum) cultivar. The plant was self-pollinated, and further selections were made on several successive generations. Excised leaves from the progeny of the selections were examined for photorespiration and net CO(2) assimilation in normal air during photosynthesis. Similar measurements were made of plants derived from selfed parents with high rates of photorespiration (ratio of (14)CO(2) released light/dark = 3.0 or greater). Efficient photosynthetic plants (greater than 22.0 mg of CO(2) dm(−2) hr(−1)) with low rates of photorespiration produced a larger proportion of efficient progeny (about 25%) than did selfing inefficient plants (about 6%), but this proportion did not increase in successive generations. Wide variations in photorespiration and photosynthesis were observed within populations of normal appearing plants grown in the same greenhouse environment. Several plants had photosynthetic rates as great as 25 mg of CO(2) dm(−2) hr(−1) coupled with light/dark ratios below 2.0. The characteristics of two representative contrasting plants were studied more extensively and were fairly constant, irrespective of leaf position on the stalk, leaf size, or time of sampling within approximately a 2-week period. One plant with a mean light/dark ratio of 1.7 showed a mean net photosynthesis of 23.4 mg of CO(2) dm(−2) hr(−1), while an inefficient plant with a light/dark ratio of 3.7 had an average photosynthetic rate of only 17.0 mg CO(2) dm(−2) hr(−1). The dark respiration was similar in these plants. Thus decreasing the photorespiratory rate by about one-half increased net photosynthesis by 38%. The results suggest that diminishing photorespiration, in an otherwise suitable genetic background, will result in large increases in net photosynthesis and plant productivity.